Posterior hybrid surgery for atlantoaxial dislocation coexisting with multilevel cervical spondylotic myelopathy - Sun, Yan; Ma, Haoning; Zhang, Zhihai; Tan, Mingsheng (Frontiers in Surgery, 2023)
Objective: To introduce hybrid surgery of posterior craniovertebral fusion plus subaxial laminoplasty for atlantoaxial dislocation (AAD) coexisting with multilevel cervical spondylotic myelopathy (CSM). Methods: A retrospective study was performed by reviewing data from 23 patients with the coexistence of AAD and CSM who underwent the Hybrid technique (n=23). Clinical outcomes, including VAS, JOA and NDI score, and radiological cervical alignment parameters including C0-2, C2-7 cobb angle and ROM were analyzed. The operation time, blood loss, surgical levels, and complications were recorded. Results: The included patients were followed up with an average of 20.91 months (range,12-36 months). Clinical outcomes including JOA, NDI and VAS scores were significantly improved at different postoperative follow-up points. C0-2, C2-7 cobb and ROM showed a stable tendency after 1 year follow-up. No major perioperative complications occurred. Conclusion: Hybrid surgery of posterior craniovertebral fusion plus subaxial laminoplasty achieved desired clinical outcomes for AAD coexisting with CSM. Moreover, it was effective in maintaining cervical alignment, proving its value and safety as an alternative technique.